2022
DOI: 10.1002/1873-3468.14341
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell adhesions in embryonic stem cells regulate the stability and transcriptional activity of β‐catenin

Abstract: E‐cadherin (CDH1) is involved in maintaining cell–cell adhesions in embryonic stem cells (ESCs). However, its function in the context of cell fate decisions is largely unknown. Using mouse ESCs (mESCs), we demonstrate that E‐cadherin and β‐catenin interact at the membrane and continue to do so upon internalization within the cell. Cdh1−/− mESCs failed to form tight colonies, with altered differentiation, marker expression and retention of pluripotency factors during differentiation. Interestingly, Cdh1−/− mESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Proteins highly enriched in JAr EVs compared to HEK EVs were implicated in cell-cell adhesion (e.g., FBLN2, ITGB4, BCAM, CDH1, ITGB5) ( Chang et al, 2017 ; Meng et al, 2020 ; Ma et al, 2021 ; Bhattacharyya et al, 2022 ), early embryo development/differentiation (e.g., FOLR1, ERVW-1, CLDN6, EPCAM) ( Moriwaki et al, 2007 ; Nagao et al, 2009 ; Strandgaard et al, 2017 ; C.West et al, 2022 ), and endometrial receptivity (e.g., ENG, MMP2, MMP14) ( Arthur et al, 2000 ; Cabral-Pacheco et al, 2020 ) suggesting a potential role of trophoblastic EV protein cargo in the embryo implantation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins highly enriched in JAr EVs compared to HEK EVs were implicated in cell-cell adhesion (e.g., FBLN2, ITGB4, BCAM, CDH1, ITGB5) ( Chang et al, 2017 ; Meng et al, 2020 ; Ma et al, 2021 ; Bhattacharyya et al, 2022 ), early embryo development/differentiation (e.g., FOLR1, ERVW-1, CLDN6, EPCAM) ( Moriwaki et al, 2007 ; Nagao et al, 2009 ; Strandgaard et al, 2017 ; C.West et al, 2022 ), and endometrial receptivity (e.g., ENG, MMP2, MMP14) ( Arthur et al, 2000 ; Cabral-Pacheco et al, 2020 ) suggesting a potential role of trophoblastic EV protein cargo in the embryo implantation process.…”
Section: Resultsmentioning
confidence: 99%
“…Among the proteins highly enriched in trophoblast analogue JAr EVs, compared to HEK-293 EVs, we found proteins linked to embryo-maternal communication, implantation, and early embryo development. FBLN2, ITGB4, BCAM, ITGB5 are some of the proteins vital in cell-cell adhesion that mediate the interactions between embryonic and maternal tissues, facilitating attachment, invasion, and completion of successful implantation ( Chang et al, 2017 ; Meng et al, 2020 ; Ma et al, 2021 ; Bhattacharyya et al, 2022 ). During the peri-implantation phase, embryos undergo differentiation that is crucial for successful embryo implantation and further development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to these findings, BMP stimulation was only able to partially disrupt E-CADHERIN/β-CATENIN junctional complex formation and E-CADHERIN localization, whereas the total protein level of E-CADHERIN remained unchanged, and the migration ability of MCF7 cells was not affected. Bhattacharyya et al previously showed that inhibition of E-CADHERIN could disrupt localization and target gene expression of β-CATENIN in mouse embryonic stem cells [69]. Therefore, E-CADHERIN may not solely depend on β-CATENIN for the cadherin complex formation, though E-CADHERIN is critical for a proper membrane localization of β-CATENIN.…”
Section: Discussionmentioning
confidence: 99%